Real-World Effectiveness, Safety, and 36-Month Persistence of Upadacitinib in Elderly Patients with Moderate-to-Severe Atopic Dermatitis: The 3–6 Month Critical Window and the Role of Early Itch Response and Psychotropic Medication Use - Yaoyao Wang; Xianzhen Chen; Yongdong Wang; Jiang Zhu; Boya Zhang; Defeng Kong; Yudan Tian; Tianze Yu; Haiyan Yu; Kejian Zhu; Hao Cheng (Journal of Clinical Medicine, 2026)
Background/Objectives: Elderly patients (≥65 years) with atopic dermatitis (AD) often carry multimorbidity and face elevated risks with Janus kinase (JAK) inhibitors. Phase III trials included few older adults, and real-world data beyond 12 months remain scarce. We evaluated 36-month efficacy, safety, and drug persistence of upadacitinib 15 mg once daily in 62 Chinese elderly patients. Methods: This retrospective cohort study was conducted at Sir Run Run Shaw Hospital (March 2022-July 2026). All patients received upadacitinib 15 mg once daily. Assessments included Week 4 pruritus Numerical Rating Scale (NRS) response, Eczema Area and Severity Index (EASI) 75/90, and Investigator’s Global Assessment (IGA) 0/1 at Weeks 12 and 24. Drug persistence was estimated with the Kaplan–Meier method (36-month cutoff), and predictors were identified by Cox regression. Results: Median age was 70.0 years, 75.8% were male, and baseline EASI was 34.5, with substantial comorbidity (Charlson Comorbidity Index [CCI] 5.0; psychotropic use 46.8%). Week 4 itch response was 70.8%. EASI 75 reached 75.0% (IGA 0/1 44.4%) at Week 12, rising to 88.0% (64.0%) at Week 24. Persistence declined from 88.7% at Month 3 to 66.1% at Month 6, the steepest drop, reaching 38.7% at Month 36. Treatment-emergent adverse events (TEAEs) occurred in 54.8% and serious adverse events (SAEs) in 8.1%, with herpesvirus infection (21.0%) being the most common event, and there were no adverse event (AE)-related discontinuations, major adverse cardiovascular events (MACE), or venous thromboembolism (VTE). In multivariate analysis, Week 4 itch response predicted longer persistence (hazard ratio [HR] = 0.203, 95% confidence interval [CI]: 0.091-0.452, p < 0.001), while psychotropic medication use predicted shorter persistence (HR = 2.814, 95% CI: 1.237-6.403, p = 0.014). Conclusions: Upadacitinib showed robust efficacy and acceptable safety over 36 months in elderly AD patients. Persistence dropped most sharply between Months 3 and 6. Week 4 itch response and psychotropic medication use independently predicted persistence. A structured Month 3 visit integrating itch reassessment, mental health screening, and dose optimization may improve long-term outcomes.